Ghosts and Their Analysts: Writing and Reading Toward Something Like Justice for Murdered or Missing Indigenous Women. (February 2016) - Granzow, Kara; Dean, Amber
We arrived late. We were doctoral students who took up as our study the "public secret" (Taussig, 1999, pg. 2) behind the contemporary disappearance of Indigenous women from the midst of the Western Canadian cities in which they, and we, were living. Suzanne Vail was there before we were, having arrived in 1987. She is the protagonist of Katherine Govier's novel Between Men, a young historian obsessively studying the 1889 murder of a young Cree woman named Rosalie in Calgary, Alberta. Reading Between Men in 2010, we found ourselves anticipated in form and obsession. That Suzanne Vail is a fiction and we are nonfiction does nothing to quiet this shock; rather, it prompts us to engage (with) her as we think through crises of ontology and epistemology in relation to what haunts contemporary efforts to frame historical remembrance of "settling" the Canadian West as a time of conquest (over land and people) and nation-building, a time of progress and development. In this article, we argue that Suzanne's obsession with Rosalie in Between Men can help us understand just how we, as scholars, are implicated in these contests over history, and explore why this might matter as we struggle toward something that might resemble justice for murdered or missing Indigenous women in the present.